Depiction of a four-armed Bharavahaka - Temples of India Project Team (Jio Institute, 2024)
A four-armed bharavahaka (load bearer) is depicted on the left pilaster of the antarala (vestibule or antechamber) of the Kaner-ki-Putli Temple. It is shown bearing the weight of the roof with its upper hands while using its lower hands to play the cymbals.